On the use of the adverbs of place ČIA and TEN in the area of Pabradė-Joniškis - Gintarė Judžentytė (Lietuvių Kalba, 2014)
The article deals with one case of the meaning of the adverbs of place čia (‘here’) and ten (‘there’) in the area of Pabradė–Joniškis. The main goal of the article is to demonstrate that in deictic situations, the adverbs čia and ten acquire new meanings. The adverbs of place under consideration are analysed in four different deictic situations: in the case of direct deixis and in imaginary deixis, to be more precise, in its three types. The research has shown that the meanings of čia and ten in deictic situations change and this shift in meaning depends on the direction of the coordinate source (origo) that a subject/agent posits or identifies with.